Integrated transcriptome and proteome analysis reveals molecular responses of soybean anther under high-temperature stress - Li, Jiajia; Chen, Linying; Zhi, Xianguan; Wang, Jianxin; Lu, Yun; Tian, Zhuo; Wu, Meiyan; Shan, Yajing; Chen, Haoran; Liao, Wei; Long, Qun; Zhu, Shangshang; et al. (Frontiers in Plant Science, 2023)
It is well documented that high temperature (HT) severely affects the development of soybean male reproductive organs. However, the molecular mechanism of thermo-tolerance in soybean remains unclear. To explore the candidate genes and regulatory mechanism of soybean response to HT stress and flower development, here, the anthers of two previously identified HT-tolerant (JD21) and HT-sensitive (HD14) varieties were analyzed by RNA-seq. In total, 219 (172 upregulated and 47 downregulated), 660 (405 upregulated and 255 downregulated), and 4,854 (2,662 upregulated and 2,192 downregulated) differentially expressed genes (DEGs) were identified between JD21 anthers treated with HT stress vs. JD21 anthers in the natural field conditions (TJA vs. CJA), HD14 anthers treated with HT stress vs. HD14 anthers in the natural field conditions (THA vs. CHA), and JD21 vs. HD14 anthers treated with HT stress (TJA vs. THA), respectively. The results showed that there were more DEGs upregulated in JD21; this might be the reason why JD21 was more HT-resistant than the HT-sensitive variety HD14. GO annotation and KEGG enriched analysis showed that many DEGs are mainly involved in defense response, response to biological stimuli, auxin-activated signaling pathway, plant hormone signal transduction, MAPK signaling pathway-plant, starch and sucrose metabolism, etc. The conjoint analysis of RNA-seq and previous iTRAQ results found that there were 1, 24, and 54 common DEGs/DAPs showing the same expression pattern and 1, 2, and 13 common DEGs/DAPs showing the opposite pattern between TJA vs. CJA, THA vs. CHA, and TJA vs. THA at the protein and gene level, respectively, among which HSPs, transcription factor, GSTU, and other DEGs/DAPs participated in the response to HT stress and flower development. Notably, the qRT-PCR analysis and physiological index change results coincided with the sequencing results of RNA-seq and iTRAQ. In conclusion, the HT-tolerant cultivar performed better under stress than the HT-sensitive cultivar through modulation of HSP family proteins and transcription factors, and by keeping key metabolic pathways such as plant hormone signal transduction normal. This study provided important data and some key candidate genes to better study the effect and molecular basis of HT on anther in soybean at a transcription and translation level.